Unfortunate Kidnapping: Tales of Destiny - "Srivastava, Pratima" (New Delhi, 2015)
The stories in this collection celebrate the journey of life - its different colours, its different forms, its ups and downs. Adversity unfolds with Ganesh's Kidnapping, compassion shows off its power with a Dramatic Rescue, as Granny's Angel Anindita discovers that it was time she swam against the tide, notwithstanding the Great Deluge that temporarily uproots Mandu's family.
Keywords: "Short Stories, Indic (English)"